2007
DOI: 10.1073/pnas.0610850104
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of trimethyllysine by a chromodomain is not driven by the hydrophobic effect

Abstract: However, whether the cationic component of the interaction is necessary for binding in the aromatic cage has not been addressed. In this article, the interaction of trimethyllysine with tryptophan is compared with that of its neutral analog, tert-butylnorleucine (2-amino-7,7-dimethyloctanoic acid), within the context of a ␤-hairpin peptide model system. These two side chains have near-identical size, shape, and polarizabilities but differ in their charges. Comparison of the two peptides reveals that the neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
170
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(193 citation statements)
references
References 35 publications
13
170
1
3
Order By: Relevance
“…7). It is interesting to note that the opposite situation has been proposed for chromodomains (37). Lysine methylation leads to a polarization of the C ⑀ -N bond increasing the cationic character of the methylammonium group and strengthening the cation-interactions with the aromatic cage but also results in an increment on the hydrophobic character of an otherwise highly polar side chain.…”
Section: Dynamics and Thermodynamics Of The Recognition Of H3k4me3 Bymentioning
confidence: 96%
“…7). It is interesting to note that the opposite situation has been proposed for chromodomains (37). Lysine methylation leads to a polarization of the C ⑀ -N bond increasing the cationic character of the methylammonium group and strengthening the cation-interactions with the aromatic cage but also results in an increment on the hydrophobic character of an otherwise highly polar side chain.…”
Section: Dynamics and Thermodynamics Of The Recognition Of H3k4me3 Bymentioning
confidence: 96%
“…1B). Three aromatic residues were shown to be necessary for assembling a methyllysine binding aromatic cage in HP1 and Polycomb chromodomains (11,12,16). Interestingly, the chromodomains of the CDYL proteins do not have the first aromatic cage residue, suggesting substantial difference in the function of this factor.…”
Section: Variability In Binding To H3 Methylated On Lys-9-mentioning
confidence: 99%
“…ability of CDY to establish more favorable polar interactions with the H3 tail than those used by HP1. Previous studies have shown that recognition of methyllysine by the HP1 chromodomain is driven by cation-interactions between the methylated ammonium group of methylated H3K9 and the side chains of three aromatic residues (11,16). The magnitude of the cationinteraction depends on the electron density of the aromatic ring, which can substantially vary from a tyrosine to a phenylalanine as well as the degree of solvent exposure in the interaction site (37,38).…”
Section: Table 2 Thermodynamic Parameters For Binding To H3 Peptides mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, trimethylation in calmodulin has been shown to modulate NAD kinase (38). Similarly, trimethylation was shown to promote interaction with polynucleotides (39) and participate in histone lysine methylation-mediated chromatin remodeling (40). A number of trimethyllysine-binding domains have been found in recent years (41).…”
Section: Monomethylation Dimethylationmentioning
confidence: 99%